Pueraria lobata polysaccharides alleviate neonatal calf diarrhea by modulating gut microbiota and metabolites - Shen, Liuhong; Shen, Yu; You, Liuchao; Zhang, Yue; Su, Zhetong; Peng, Guangneng; Deng, Junliang; Zuo, Zhicai; Zhong, Zhijun; Ren, Zhihua; Yu, Shumin; Zong, Xiaolan; et al. (Frontiers in Veterinary Science, 2023)
Neonatal calf diarrhea (NCD) is still one of the most critical diseases in calf rearing. Studies have shown that Pueraria lobata polysaccharides (PLP) have intense antioxidant and immunomodulatory activity and modulate gut microbiota. This randomized clinical trial aimed to determine the effect of PLP on the neonatal calf with diarrhea. In this study, we recorded the fecal score of experimental calves, and calves with fecal scores ≥ 2 were determined as diarrhea and assessed their serum concentrations of inflammatory cytokines and oxidative damage-related indices. Fecal microbiota and metabolomics of diarrheal calves were further investigated. Results showed that treatment with PLP decreased the fecal score of diarrheal calves, serum concentrations of IL-1β, TNF-α, and malondialdehyde, and also elevated the level of superoxide dismutase. In addition, PLP treatment altered the gut microbiota, significantly increased the relative abundances of beneficial bacteria, including the phyla Bacteroidetes and Actinobacteria, the genus Collinsella, Megamonas, and Bifidobacterium; decreased the relative abundances of pathogenetic or diarrhea related bacteria, such as Proteobacteria, Fusobacteria, Clostridium_sensu_stricto_1, and Escherichia_Shigella. Moreover, PLP can increase the fecal concentrations of isobutyric acid, propionic acid, and pantothenate; lower the levels of PC (18:0/18:1(9Z)), arachidonic acid, and docosahexaenoic acid. Thus, the results suggested that the PLP may perform the therapeutic activity via alleviating intestinal inflammation and regulating gut microbiota, avoiding further dysbiosis to restore the metabolism of gut microbiota, and finally promoting the recovery of diarrhea. The change further mitigated intestinal inflammation and oxidative damage in diarrheal calves. This indicated that PLP might be a promising treatment to attenuate diarrhea in neonatal calves.